Correlation of Abdominal CT scan Score and Alpha-fetoprotein Levels in Hepatocellular Carcinoma - Indira Prawita Martani; Firman Sitanggang; Ni Margiani; I Gde Widiana; Made Asih; I Made Ayusta (International Journal of Integrated Health Sciences, 2022)
Objective: To assess the correlation between the Alpha-fetoprotein (AFP) level and characteristics of liver lesions listed in the abdominal computed tomography (CT) scan scores in hepatocellular carcinoma.Methods: This was a retrospective analytic observational study with a cross-sectional design conducted at Sanglah Hospital in January 2017–January 2021. Subjects were patients diagnosed with hepatocellular carcinoma based on clinical and laboratory features. Samples were taken by consecutive sampling. The results of the abdominal CT scan were read by two radiologists with a predetermined abdominal CT scan scoring system. The AFP level data were taken at a maximum of 5 days before an abdominal CT scan was performed.Results: A total of 64 subjects were included in this study. The mean serum AFP level was 1,000 IU/mL (range 0.54–61830 IU/mL). The mean abdominal CT scan score by examiner one was 10.093±5.59, while the examiner two provided a score of 10.281±5.45. The difference in mean CT scan scores between the two examiners was very low and insignificant (mean difference score -0.188; 95% CI -1.894–1.519). The rho Spearman value was 0.918 (p<0.001) between serum AFP levels and abdominal CT scan scores. In the partial correlation, the value of r=0.678 (p<0.001) was obtained after controlling for body mass index (BMI), age, and sex variables.Conclusions: There is a strong positive correlation between serum AFP levels and abdominal CT scan scores in hepatocellular carcinoma patients. Further research is needed with a prospective design to reduce research bias.